Doações para ONGs no Brasil : estudo de casos e análise FSQCA - Umebayashi, Micheli (2018)
Purpose: To analyze if the mechanisms that lead Brazilians to donate organizations (NGOs) are similar to those other countries to have this behavior, in addition to a comparison between the factors contextuals that seek to explain why some countries are more generous than others. Methodology: Case study conducted from 25 interviews in depth (a database of donors and non-donors of a Brazilian organization large) submitted to content analysis and then to Fuzzy analysis Qualitative Comparative Analysis. Conclusion: There are differences between the mechanisms proposed in the literature and what was observed in the interviewee. The presence of a trigger - an internal event or important in the life of the individual - can be determinant for the donation to take place. It was also verified that there is a negative perception about the performance of NGOs, their role and importance in society and the image of an inefficient and corrupt government, factors that may be associated with the country's low performance in the global ranking of Philanthropy. Originality: Contribute to the extension and validity of studies carried out developed countries, insofar as the theories donors from a country in the Southern Hemisphere, with an average HDI and a culture of unrestrained giving. In addition, contributing to the construction of a theoretical framework on donation in Brazil and generate knowledge about Brazilian donors, in order to support professionals working in non-governmental develop their activities in the country